2012
DOI: 10.1093/rheumatology/kes093
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 promotes destabilized angiogenesis by modulating angiopoietin expression in rheumatoid arthritis

Abstract: IL-6 not only enhances VEGF expression but also inhibits Ang-1 signalling by directly down-regulating Ang-1 expression and up-regulating Ang-2, an antagonist of Ang-1. These synergistic effects may play a critical role in destabilized angiogenesis in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…RA angiogenesis is driven and maintained by proangiogenic factors released from RA synovial tissue myeloid cells and fibroblasts, which include vascular endothelial growth factor (VEGF), angiopoietin (Ang)1 and 2, plateletderived growth factor, and transforming growth factor-β [3][4][5]. VEGF is the most potent proangiogenic factor in RA angiogenesis, highly expressed in RA [6], stimulating endothelial cell (EC) proliferation, migration, and vascular tube formation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA angiogenesis is driven and maintained by proangiogenic factors released from RA synovial tissue myeloid cells and fibroblasts, which include vascular endothelial growth factor (VEGF), angiopoietin (Ang)1 and 2, plateletderived growth factor, and transforming growth factor-β [3][4][5]. VEGF is the most potent proangiogenic factor in RA angiogenesis, highly expressed in RA [6], stimulating endothelial cell (EC) proliferation, migration, and vascular tube formation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ang1, Ang2, Tie1, and Tie2 are upregulated in RA synovial tissues [10]. Evidence suggests that the Ang/Tie2 signaling pathway mediates the proangiogenic effects of tumor necrosis factor alpha (TNF-α), interleukin (IL)-6, and tolllike receptor (TLR)2 in RA [5,11,12]. Ang2 neutralization decreases synovial inflammation, neovascularization, and joint destruction in CIA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the cytokines closely related to the pathogenesis of s-JIA, previous studies have shown that IL-1b downregulates Ang-1 expression [17]. Furthermore, IL-6 inhibits Ang-1 signaling by downregulating Ang-1 expression and upregulating Ang-2 expression [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of Ang-2/1 in the homeostasis of endothelial function, several lines of evidence have suggested that Ang-1 and Ang-2 play roles in the exacerbation of synovitis in patients with rheumatoid arthritis (RA) [18,20,21]. Ang-1, Ang-2, and Tie2, are expressed in RA synovial tissue [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation